PERSPEKTIF MAHASISWA TERHADAP PENGARUH INVESTASI BODONG BAGI KESEHATAN MENTAL - Firda Amelia; Husnul Khatimah; Nur Hidayah; Nurmadina; Riska Ridha Adika; Pandu Hyangsewu (Jurnal Sosial Humaniora dan Pendidikan, 2024)
This study uses a quantitative approach. The population in this study is all students who are potential subjects. Sampling was carried out using the purpose sampling method. The research instrument is a questionnaire that is distributed online to respondents who meet the criteria that have been determined. this study aims to (1) Identify the influence between the views of students on investment fraud with their mental condition (2) analyze the views of students related to the risks and losses of investment fraud. This study shows that although theoretically bulging investments can have a negative impact on mental health, such as stress, anxiety, and feelings of insecurity, the results of data analysis did not find a significant relationship between the experience of bulging investments and students ' mental health conditions. The relationships found were negative but very weak and not statistically significant. This indicates that the impact of student mental health may be influenced by other factors beyond the experience of bulging investments.